ANALISIS YURIDIS TERHADAP PUTUSAN BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) DALAM PENYELESAIAN SENGKETA KONSUMEN (Studi Putusan Nomor 006/SPut/IX/2025/BPSK.Mdn) - Rahmat Rahmat Tri Andika Debataraja; Martono Martono Anggusti (Cattleya Darmaya Fortuna, 2025)
Consumer disputes hold significant importance in Indonesia due to the large number of business actors, which necessitates the establishment of the Consumer Dispute Settlement Agency (BPSK) as stipulated in Law Number 8 of 1999 on Consumer Protection. This study examines the relevant legal provisions and their alignment with the BPSK Decision No. 006/SPut/IX/2025/BPSK.Mdn, covering both fundamental regulations and consumer protection aspects. Using a normative juridical approach and referring to primary, secondary, and tertiary legal materials, the research findings indicate that BPSK operates in accordance with existing legal frameworks and upholds the principles of justice, legal certainty, and balance between consumers and business actors. Consequently, the implementation of the law and its decisions are consistent with the foundational principles of the Consumer Dispute Settlement Agency.